Properties and applications of additively manufactured metallic cellular materials: A review. (April 2022) - du Plessis, Anton; Razavi, Seyed Mohammad Javad; Benedetti, Matteo; Murchio, Simone; Leary, Martin; Watson, Marcus; Bhate, Dhruv; Berto, Filippo
Abstract: Additive manufacturing (AM) refers to a collection of manufacturing methods involving the incremental addition of material to build a part directly in its final or near-final geometry, usually in a layer-by-layer process. Metal AM in particular has seen great industrial adoption and maturation. This technology enables increased freedom of design in engineered materials with complex geometries, of which architected cellular or lattice structures are particularly promising in a wide range of applications. These materials are similar to stochastic foams which have found many industrial applications over the last few decades, but regular cellular structures possess a higher degree of control over the manufactured architectures made possible by additive manufacturing. These architected porous materials have properties that can be fine-tuned for a particular application (for mechanical performance, permeability, thermal properties, etc.). The control over the design and manufacturing of such architected structures in comparison to stochastic structures opens new application possibilities and enables a range of new products and features. This potential is only starting to be realized as metal AM techniques are maturing and are increasingly being adopted in various industries, and as design-for-AM capabilities improve. This review paper summarizes the unique properties of AM lattice structures and how these have been successfully employed for specific applications so far, and highlights various application areas of potential interest for the near future. The focus in this review paper is therefore on unique achievable properties and the associated applications for metal additively manufactured lattice structures.